1989
DOI: 10.1080/03057078908708205
|View full text |Cite
|
Sign up to set email alerts
|

Trees in fields in Southern Zimbabwe

Abstract: Journal of Southern African StudiesPublication details, including instructions for authors and subscription information:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(43 citation statements)
references
References 5 publications
1
42
0
Order By: Relevance
“…For example, studies of children in miombo areas have demonstrated how wild fruits, rodents, insects and birds can form a crucial source of foods for children from poorer households while at school (those from better-off households being sent to school with food or money) or while herding (Campbell et al 1991a;Coote et al 1993a;McGregor 1995a). It is partly for this reason that children can display remarkable knowledge of the local woodland resource, with mental fruit tree maps and nicknames for the sweetest fruit trees (Wilson 1989a).…”
Section: Other Dimensions Of Differentiationmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, studies of children in miombo areas have demonstrated how wild fruits, rodents, insects and birds can form a crucial source of foods for children from poorer households while at school (those from better-off households being sent to school with food or money) or while herding (Campbell et al 1991a;Coote et al 1993a;McGregor 1995a). It is partly for this reason that children can display remarkable knowledge of the local woodland resource, with mental fruit tree maps and nicknames for the sweetest fruit trees (Wilson 1989a).…”
Section: Other Dimensions Of Differentiationmentioning
confidence: 99%
“…Indigenous technical knowledge clearly underlies both use and management of trees and woodlands. Knowledge about the taxonomy, ecology, silviculture and uses of trees and woodlands is widespread amongst rural populations throughout the region, as ethnobotanical surveys testify (Wilson 1989a;Tuite and Gardiner 1990a;Matowanyika 1991;McGregor 1991;Coote et al 1993a;Sørensen 1993). …”
Section: Gender and Trees (Continued)mentioning
confidence: 99%
See 2 more Smart Citations
“…Research in the social relations of common property systems in Africa reveals a seemingly endless variety and complexity of rights, obligations, and rules, many of them ad hoc (Bassett and Crummey 1993). Rights to a particular area of land may have multiple claims upon it, both group and individual, and can include rights to water, fuel, grazing, and cultivation plots, which in turn may vary according to season, species, or intended usage (Fortmann and Bruce 1988;Wilson 1989;Neumann 1992a;Campbell 1993). …”
Section: Questionable Assumptions and Contradictory Designsmentioning
confidence: 99%